THE DEVELOPMENT AND COURSE OF CHRONIC PYELONEPHRITIS AGAINST THE BACKGROUND OF DYSMETABOLIC NEPHROPATHY IN CHILDREN - Baratova Ra’no Shomuratovna (Web of Journals Publishing, 2024)
A number of studies have proven the role of combined immunological insufficiency in the pathogenesis of secondary chronic pyelonephritis in children, and therefore various variants of immunocorrective therapy have been developed. In most cases, it was carried out. monoimmunocorrection in various diseases, including chronic pyelonephritis, i.e. stimulation of one of the links of immunity, which can be acceptable only if the patient has an isolated lesion of one of the links of the immune system. The aim of our study was to study the effectiveness of step-by-step sequential targeted immunocorrection in secondary chronic pyelonephritis against the background of purine dysmetabolism. Materials and methods. 76 children aged 3 to 15 years inclusive were examined, diagnosed with secondary chronic pyelonephritis on the background of hyperuricemia and hyperuricosuria with signs of activity of the renal microbial inflammatory process. Results and discussion. The initial immunological parameters of group 2 patients were characterized by the fact that the relative content of T-lymphocytes was significantly reduced compared to the control (49.92± 1.52% : p<0.01 see Tab. 1). Conclusions. The results of the conducted studies indicate that secondary chronic pyelonephritis against the background of hyperuricemia and uraturia proceeds with pronounced shifts in the body's immune system, and they are combined.
Keywords: children, pyelonephritis, dysmetabolic nephropathy.